Revisiting CA6 formation in cement-bonded alumina-spinel refractory castables - Tomba Martinez, Analia Gladys (2017)
This work revisits the proposed mechanisms presented in the literature for CA6 formation in Al2O3-MgO and Al2O3-MgAl2O4 castables bonded with calcium aluminate cement. New experimental tests, thermodynamic simulations and re-evaluation of the chemical composition and microstructural aspects observed for samples fired in the temperature range of 1150°C to 1500°C were carried out. Based on these data, a new interpretation of the CA6 generation process, as well as the features which influence the location and morphology of this phase were proposed. CA6 formation via solid and liquid states are suggested to take place in all evaluated compositions, where the former (solid-state) is the main reaction predicted for the silica-free refractories (AM0MS and AS0MS), whereas the liquid-state one prevails in the AM1MS and AS1MS materials. The CA6 crystal morphology should be affected by these different reaction mechanisms. According to the experimental results, it was also discussed the role of the calcium hexaluminate features in the overall corrosion behavior of the designed refractories when they were placed in contact with molten slag at high temperatures. Such aspects have not been previously reported in published papers related to this subject.